Shopping centers versus traditional open street bazaars: A comparative study of user’s preference in the city of Karachi, Pakistan - Iqbal, Asifa; Nazir, Humaira; Memon, Reena Majid (Frontiers in Built Environment, 2022)
Bazaars have always been a center of social, economic, and cultural exchange. Bazaars as public spaces were responsible for creating an ideal public setting to enhance social interactions for everyone. However, over a period of time, the concept of Bazaars has changed. Modern shopping centers seem to be an appropriate alternative to bazaars in terms of accessibility, quality of space, maintenance, sense of safety and security, and leisure activities. Karachi, being the commercial hub of Pakistan, hosts a load of business centers and marketplaces around the city. However, parts of the old bazaars in Karachi have been slowly destroyed to make room for wider streets and roads in Karachi, and new forms of shopping centers have been emerging across the city. This research will investigate the preference of people for bazaars vs. shopping centers and the attribute of shopping centers that aided in their preference. This aim will be achieved by 1) understanding the evolving concepts of public spaces in Karachi and 2) investigating people's preference for shopping centers vs. Bazaars and the impact of services offered by shopping centers on user satisfaction. A comparative case study technique is used. Data is collected through an online survey in relation to a traditional bazaar and a newly built shopping center in Karachi, Pakistan. The finding results show that the success of shopping centers is generally influenced by indicators like atmosphere, safety, accessibility, and leisure activities while people visit traditional open street bazaars in Karachi for the economical prices and accessibility to public transportation. On the other hand, the avoiding behavior of users towards traditional bazaars is reported due to narrow pathways, unmaintained environment, no parking and toilet facilities, and a large influx of people. Although these results are not the first ones in the literature, they are new in relying on findings from a cosmopolitan city in Pakistan. Finally, this study provides some recommendations that can serve urban planners and other practitioners to integrate these indicators at the earliest conceptual design phases when planning and managing open street bazaars in developing countries.